Studies of Semen Qualities of Lahore Pigeons (Columba livia) (Global Journal of Medical Research, 2018)
Ejaculation capabilities and semen characteristics depending on seasonal variations are presented in this paper. The mean temperature range in the study area was 25.6°C (February) -30.5°C (May) and the mean humidity range was correspondingly between 62.5-80.4% (February) and 77.6-83.3% (May). The photoperiod was minimum in February (13h/day) and maximum in May (15.6h/day). Out of 927 collection attempts, 509 attempts ended with successful ejaculation and hence the semen collection rate was 54.9±8.8%. The highest ejaculation rate was 65% in March followed by 63.7% in November, whereas it was low (44.7%) in September. Average volume of semen ejaculated from a bird in one collection was 9.3±1.5µl and the range was 6.1 ± 0.2 µl (September) -10.8 ± 0.7 µl (November)/ collection (p>0.05). The average semen concentration was 4.01±0.5×10 9 /ml.
Keywords: lahore pigeon; semen quality; semen ejaculation and season